AN INVESTIGATION OF LUBRICATION CHARACTERISTICS AND PARAMETERS INFLUENCE ON MAIN BEARING IN HORIZONTAL DIESEL ENGINE - JIA DeWen; BAI JianYong; BI YuHua; ZHANG JianGang; DENG Wei; MA XinHua (Jixie qiangdu, 2016)
Based on the horizontal two-cylinder diesel engine,the main bearing elastohydrodynamic lubrication model was constructed in AVL EXCITE PU software,some results were acquired at the maximum torque working condition（ 1600 r / min）under the consideration of the roughness of bearing bush and journal. The results showed that three main bearings’ minimum film thickness and maximum film pressure satisfy the design criterion. The 2nd main bearing ’s maximum film pressure is about150 MPa which is the oil pressure limits. The 2nd main bearing orbit was obvious centripetal movement,which showed that the2 nd main bearing had obvious bending moment. The bending moment was considered to analysis object,and the parameters influence to bending moment is width of main bearing,bearing clearance,oil groove width and oil port position with the orthogonal experimental design.